Case report: successful perioperative management of patients with haemophilia A using an extended half-life factor VIII (Efmoroctocog alfa) during neurosurgical procedures - Kocher, Florian; Seeber, Andreas; Kerschbaumer, Johannes; Schmidt, Stefan; Wolf, Dominik; Feistritzer, Clemens (Therapeutic advances in hematology, 2021)
Patients with haemophilia A (HA) undergoing neurosurgical procedures have a high risk of haemorrhage with potential fatal outcome. Here, we present a successful perioperative haemostatic concept applying an extended half-life factor VIII (EHL FVIII), Efmoroctocog alfa, in two patients with HA undergoing neurosurgery for paramedian right-sided disc herniation (case 1) and astrocytoma (case 2). After adequate EHL FVIII treatment the surgical procedures were performed without any bleeding complications despite the high-risk interventions. Laboratory measurements confirmed stable FVIII levels throughout the hospital stay. We suggest close interdisciplinary collaboration between involved clinicians as mandatory prerequisite for an optimized perioperative management in patients with HA. The presented cases indicate, that the increased stability, safety and fewer injections provide a rationale to use EHL FVIII products in HA patients undergoing surgical interventions with a very high bleeding risk.